Impact Pengaruh media sosial facebook terhadap minat kunjungan wisatawan pada objek tuur ma'asering tomohon - DEISY CHRISTINA ANDIH (PolimdoSains, 2022)
Tuur Maásering is one of the attractions that is now a favorite for tourists to fill their holidays or activities in their free time both with family and friends. Tuur Maásering is a tourist attraction which besides the coolness of its location also offers natural beauty with palm trees and huts made of bamboo. The Tuur Maásering tourist attraction also presents local Minahasa wisdom by serving traditional Minahasa drinks, namely rat stamp. Not only serving Minahasa specialty drinks, but this Tuur Maásering object also presents a way of distilling traditional Minahasa drinks that can be seen by tourists. After the election of the Regional Leader of North Sulawesi, tourist visits have decreased due to the Pandemic situation. However, in early March the Tuur Maásering tourist attraction, from the results of observations, tourist interest in visiting this attraction has increased and since June, tourist visits have drastically decreased due to the COVID-19 pandemic. This research method is carried out using descriptive quantitative methods. The ease of accessing information and communication and supported by increased community mobilization has also triggered the development of various industrial sectors, including the tourism industry. This has an impact on increasing the number of visits to various tourist objects. Facebook social media is one that affects the interest of tourists visiting the tourist attraction Maásering